Pengukuran Sektor Ekonomi Unggulan Kabupaten Sambas: Tipologi Klassen Dan Analisis Shift-Share - Alabshar, Nufi; Liantin, Nugra (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2024)
Abstract. Economic growth refers to the development of an area's economy. The Sambas district, located in Kalimantan Barat Province and home to two cross-border posts, requires careful planning for its development programs in this strategically important area. This study aims to identify the economic sectors with the highest priority in Sambas Regency, which can be the focus of local economic development. Using Gross Regional Domestic Product data and quadrant analysis of Klassen typology and shift-share analysis, the results indicate that the Agriculture, Forestry, and Fishing sector is a priority sector for development without neglecting other sectors. This study significantly enhances the understanding of regional economic sectors and contributes meaningfully to the development of the local economy, particularly in Sambas Regency. Keyword: dynamic location quotient, economic growth, klassen typology, sambas regency, shift-share analysis.